OPINI MASYARAKAT TERHADAP KOMUNIKASI KEPEMIMPINAN PERANGKAT DESA DALAM PENINGKATAN PEMBANGUNAN DI DESA KINEPEN KECAMATAN MUNTHE TAHUN 2019 - Emmelia A. Ginting; Verawati br Sembiring (JURNAL SOCIAL OPINION: Jurnal Ilmiah Ilmu Komunikasi, 2021)
This study aims at determining public opinion on village apparatus leadership communication used by the Village Apparatus in an effort to improve development in Kineppen Village, Munthe District, Kab. Karo. The research subjects were the Kineppen Village Community, Religious Leaders, Community Leaders and also the Village Apparatus themselves. The object of this research is Leadership Communication, especially Qualitarian Stlye Theory. The data processing uses a qualitative descriptive approach. The results of the descriptive analysis show that from Public Opinion, the implementation of the leadership communication function is quite good, but weaknesses are still found in the Informative and Persuasive functions in an effort to increase development. And based on the Leadership Communication Theory, namely The Equalitarian Style which has an Indicator of Familiarity, public opinion feels quite close to the Village Apparatus who serve them at the Village Office, but the village head is considered less familiar with the residents. Indicators of Understanding/Openness, Community opinion about village apparatus is considered to be willing to pay attention to residents by accepting and responding to residents' complaints, both about the distribution of basic necessities, fertilizers for farmer groups, and others. However, the Village Head is considered to be less open and lack of two-way communication, causing obstacles in improving public services and increasing village development. Sociability indicator, in this field, the people of Kineppen Village are of the opinion that the Village Apparatus is quite flexible in fostering good relations with the village community, but their opinion about the Village Head is considered to be less sociable with the residents because they rarely want to socialize since serving as Kineppen Village Head.